Irradiation of Er3+, Yb3+ doped phosphate glasses using electrons and protons. Issue 16 (November 2020) - Sen, R.; Mihai, L.; Straticiuc, M.; Burducea, I.; Ighigeanu, D.; Sporea, D.; Petit, L.
Abstract: Radiation effects on phosphate glasses with the system (98-x) (0.50P2 O5 -0.40SrO-0.10Na2 O) −0.5Er2 O3 -1.5Yb2 O3 -xZnO (in mol %) with x ranging between 0 and 5 were investigated using radiations by electrons and protons. Changes in the optical and structural properties were observed after both irradiations, the changes of which depend on the doses. Due to its higher dose and longer irradiation time, the proton beam exposure leads to the formation of a larger amount of defects in the network, which is suspected to expand during the irradiation as evidenced using Raman spectroscopy. Both radiation treatments were found to also increase the intensity of the emission at 1.5 μm. The glass with x = 5 was found to be the most sensitive to both radiation treatments probably because of the addition of Zn which not only depolymerizes the glass network but also leads to the formation of Zn defects. Finally, we confirm that the photo-response of the investigated glasses is a reversible process using a heat treatment near the glass transition temperature of the glasses.